Impact of negative affectivity and trait forgiveness on aortic blood pressure and coronary circulation. (5th September 2014) - Sanchez‐Gonzalez, Marcos A.; May, Ross W.; Koutnik, Andrew P.; Fincham, Frank D.
Abstract: Prior research suggests that negative affectivity (NA) may have a direct adverse effect on coronary circulation, whereas forgiveness may provide cardioprotection. This study examined whether NA and forgiveness were independently related to aortic hemodynamics and the subendocardial viability index (SVI), a marker of coronary perfusion. A sample of 131 adults ( M  = 21.11 years, SD  = 2.52) were evaluated for NA (depression, anxiety, and anger symptoms) and forgiveness (Tendency to Forgive Scale; TTF). Aortic hemodynamic parameters via applanation tonometry were assessed at rest and during sympathostimulation (cold pressor test; CPT). Hierarchical multiple regression analyses of resting values showed that NA was related to higher aortic blood pressure (ABP) and lower SVI. After controlling for demographics and for NA, TTF scores were significantly associated with decreased ABP, but increased SVI. CPT changes from baseline indicated that, after controlling for demographics and NA, TTF scores were significantly associated with SVI. Results indicate that NA significantly predicts ABP and decreased SVI. Conversely, forgiveness seems to provide cardioprotection by evoking decreased ABP while improving SVI.